A Management System for Car Maintenance Services - Lai, Zhi Yuan; Mohmad Hassim, Yana Mazwin (Applied Information Technology And Computer Science, 2021)
The web-based Vision car service shop management system is a system proposed to aid in business management by providing business processes systemization to Vision car service. Vision car service shop currently face a significant problem in business operation which is heavy workloads due to massive manual business process. The purpose of developing this system is to overcome the problems by aiming to initiate business process systemization through conversion of manual documentation works to system-based works. This proposed web-based system is designed based on users’ requirements and it consists of 4 modules which are register and login module, document management module, inventory module and report generating module. Through this system, employees of Vision car service can create, read, update and delete document information provided by system functionalities, generate sales and inventory reports as well as manage inventory stocks. Proposed system will be developed using Sashimi Waterfall model as the system development life cycle and system architecture are defined using structure approach. The system will provide functionalities to users through the 4 modules defined in scope and based on user requirements while fulfilling system requirements. The constraint of this system includes the propose system is only available on personal computer and data security as well as reliability. It is expected that the system will help Vision car service shop to manage documents, inventory and reports with ease and efficiently.